23 Performance of the grace 2.0 score in patients with type 1 and type 2 myocardial infarction. (17th July 2020) - Hung, John; Roos, Andreas; Kadesjo, Erik; McAllister, David; Shah, Anoop SV; Anand, Atul; Strachan, Fiona E; Fox, Keith AA; Mills, Nicholas L; Holzmann, Martin; Chapman, Andrew R
Abstract : Introduction: The Global Registry of Acute Coronary Events (GRACE) score was developed to evaluate risk in patients with myocardial infarction. However, its performance in type 2 myocardial infarction is uncertain. Methods: In two cohorts of consecutive patients with suspected acute coronary syndrome from ten hospitals in Scotland (n=48, 282) and a tertiary care hospital in Sweden (n=22, 589), we calculated the GRACE 2.0 score to estimate death at one year. Discrimination was evaluated by the area under the receiver-operator-curve (AUC), and compared for those with an adjudicated diagnosis of type 1 and type 2 myocardial infarction using DeLong's test. Results: Type 1 myocardial infarction was diagnosed in 4, 981 (10%) and 1, 080 (5%) patients in Scotland and Sweden, respectively. At one year, 720 (15%) and 112 (10%) patients died with an AUC for the GRACE score of 0.83 (95% confidence interval [CI] 0.82 to 0.85) and 0.85 (95% CI 0.81 to 0.89). Type 2 myocardial infarction occurred in 1, 121 (2%) and 247 (1%) patients in Scotland and Sweden respectively, with 258 (23%) and 57 (23%) deaths at one year. The AUC was 0.73 (95% CI 0.70 to 0.77) and 0.73 (95% CI 0.66 to 0.81) in type 2 myocardial infarction, which was lower than for type 1 myocardial infarction in both cohorts (P<0.001 and P=0.008, respectively). Conclusions: The GRACE score provided good discrimination for all-cause death at one year in patients with type 1 myocardial infarction, and moderate discrimination for those with type 2 myocardial infarction. Conflict of Interest: None